Psychological features of creative and innovative thinking of managers - Lutfullaeva Nigora (Zien Journals, 2023)
New types of thinking that have come to the attention of researchers in the last decade include innovative and creative ones. Innovative thinking is alien to the usual logic, because the basis of innovative activity is creativity. The innovative and creative thinking of the leader has common denominators, and together with managerial abilities leads to different results in the organization. For example, somewhere in a company, organization, a new product may appear, or it may not, that is, it may remain in words, in ideas, business plans. A successful manager is one who combines these two types of thinking
Keywords: innovative intelligence; practical intelligence; logic